2018
DOI: 10.1016/j.jnt.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Refined dimensions of cusp forms, and equidistribution and bias of signs

Abstract: We refine known dimension formulas for spaces of cusp forms of squarefree level, determining the dimension of subspaces generated by newforms both with prescribed global root numbers and with prescribed local signs of Atkin-Lehner operators. This yields precise results on the distribution of signs of global functional equations and sign patterns of Atkin-Lehner eigenvalues, refining and generalizing earlier results of Iwaniec, Luo and Sarnak. In particular, we exhibit a strict bias towards root number +1 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…It can be observed that the determination of the precise type of symmetry, among the three orthogonal ones, depends on the proportion of automorphic forms having sign −1 in the functional equation. Such information is not available in the level of generality of this paper; however, with mild assumption on the conductor, Martin [21] shows (despite an interesting bias) that the limiting proportion is 1/2, pleading for an orthogonal type of symmetry for A(G). The family restricted to positive (resp.…”
Section: Type Of Symmetry Of Quaternion Algebrasmentioning
confidence: 93%
“…It can be observed that the determination of the precise type of symmetry, among the three orthogonal ones, depends on the proportion of automorphic forms having sign −1 in the functional equation. Such information is not available in the level of generality of this paper; however, with mild assumption on the conductor, Martin [21] shows (despite an interesting bias) that the limiting proportion is 1/2, pleading for an orthogonal type of symmetry for A(G). The family restricted to positive (resp.…”
Section: Type Of Symmetry Of Quaternion Algebrasmentioning
confidence: 93%
“…In the case of N squarefree, building on previous works of Yamauchi, Skoruppa and Zagier, Martin gave a formula [18,Equation (1.6)] for the trace of the Atkin-Lehner operator W p on S k (Γ 0 (pN )). In the simple case where N = q > 3 is a prime and p > 3, we have…”
Section: Dimension Formulaementioning
confidence: 99%
“…In this step, we actually only compute the dimension d ε of such eigenspaces. As shown in Section 4, this computation can be done via Corollary 4.2, Equation (1.6) in [18] and by recursion.…”
Section: Dimension Formulaementioning
confidence: 99%
See 1 more Smart Citation
“…Remark 4.2. Applying the trace formula to compute the trace of products w i 1 · · · w i k acting on S 2 (N, Q) new , Martin [12] shows that d χ,Q := dim Q S 2 (N, Q) new,χ all roughly equal d/2 s . This does not directly imply the above assumption, since d χ,Q does not generally equal d χ .…”
Section: 1mentioning
confidence: 99%